Are you ready for a child? A methodological triangulation on fertility intentions in Austria - Isabella Buber; Katrin Fliegenschnee (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2011)
Research on fertility has been mainly using quantitative methods, and it is only in the last few decades that qualitative research methods have become more common in demography. Combining qualitative and quantitative methods in a so-called triangulation is even more uncommon. Applying a triangulation, the current paper aims to better understand the concept of fertility intention with regard to family formation. During problem-centred interviews with childless men and women, the issue of feeling ready was mentioned again and again. It turned out that apart from economic circumstances, this individual aspect is important for the decision to have a child. In this paper, we explain the rather complex concept of feeling ready using interviews. Based on these qualitative results, additional questions were included in the Austrian 'Generations and Gender Survey' (GGS) which allow to analyse the dimension of being ready also quantitatively in a national representative dataset. Our results clearly support the theory of planned behaviour in the context of family formation, as social norms, attitudes and behaviour control are significantly associated with childbearing intentions. In the contextual framework of the theory of planned behaviour, our quantitative results revealed that the feeling of being ready has additional explanatory power for childbearing intentions among childless men and women in Austria.
Keywords: 300; Fertility intentions; triangulation; mixed methods; theory of planned behaviour; Austria; GGS; Fertilität; Zeit; Familienplanung; Privater Haushalt; Österreich